2005
DOI: 10.1007/s00464-004-2118-2
|View full text |Cite
|
Sign up to set email alerts
|

Early peritoneal macrophage function after laparoscopic surgery compared with laparotomy in a mouse mode

Abstract: Reduced phagocytosis 1 h after surgical interventions suggests a contribution of PMo to the altered immune function. When exposed to CO2, PMo show a decreased basal TNF-alpha release. However, PMo also show an increased TNF-alpha release after a second immune stimulation (E. coli), suggesting a greater competency of interaction in an immune defense reaction after CO2 exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…In line with the fact that the Treg cell compartment is extended after trauma and sepsis [37] there was no difference between the CO 2 insufflation and the sham anesthesia control group. The findings suggest that both groups with air exposure of the peritoneal cavity have more pronounced immune alteration, a finding that was also observed in our former studies [22,23]. This finding may closely be linked to the suppressed recall immunity in terms of delayed type hypersensitivity during the four postoperative days in mice exposed to laparotomy observed earlier [8].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In line with the fact that the Treg cell compartment is extended after trauma and sepsis [37] there was no difference between the CO 2 insufflation and the sham anesthesia control group. The findings suggest that both groups with air exposure of the peritoneal cavity have more pronounced immune alteration, a finding that was also observed in our former studies [22,23]. This finding may closely be linked to the suppressed recall immunity in terms of delayed type hypersensitivity during the four postoperative days in mice exposed to laparotomy observed earlier [8].…”
Section: Discussionsupporting
confidence: 74%
“…Especially CO 2 insufflation showed no difference to air in regard to systemic TNF production. This stands in sharp contrast to local peritoneal TNF production which is increased in non-stimulated peritoneal macrophages after in vivo air exposure of the peritoneal cavity [22]. One may hypothesize that for splenocyte stimulation tissue trauma is more relevant than the type of peritoneal gas exposure and its consecutive inflammatory response.…”
Section: Discussionmentioning
confidence: 73%
“…Because no difference was found in the apoptosis markers of peritoneal macrophages among the groups, apoptosis seems not to be an explanation for different clearance rates. Trypan blue testing at the first centrifugation step underscored the very high viability of cells and no difference among the groups in this or our previous work [19], suggesting that no major amount of late apoptotic or necrotic cells would be Trypan blue positive. 5.…”
Section: Discussionmentioning
confidence: 65%
“…Recently, we were able to demonstrate that all invasive interventions reduced the early postoperative ex vivo phagocytosis of peritoneal macrophage (PMo), as compared with sham controls, early after surgery. We also showed that tumor necrosis factor (TNF)-a release by macrophages after ex vivo Escherichia coli exposure was diminished in the abdominal air exposure groups, as compared with the carbon dioxide (CO 2 ) insufflation groups [19]. There is substantial evidence that one difference between groups may be mediated by the biologic effects of the two different gas types.…”
mentioning
confidence: 92%
“…As a first line of defense, the local macrophages and neutrophils (polymorphonuclear neutrophils) are of major importance in protecting the organ. Air exposure triggers a higher transmigration (from blood to peritoneum) and decreases apoptosis of polymorphonuclear neutrophils in the face of CO 2 exposure [26,27]. The minimally invasive character of laparoscopic surgery reduces the surgical insult to the peritoneum and probably provokes a reduced antigenic exposure to the cell-mediated immunological system [28].…”
Section: Discussionmentioning
confidence: 99%